20 years review of antenatal diagnosis of haemoglobin Bart's disease and treatment with intrauterine transfusion. (8th March 2022) - Hui, Pui Wah; Pang, Polly; Tang, Mary H. Y.
Abstract: Objective: To review prenatal diagnosis and outcome of alpha thalassaemia major through universal antenatal screening. Method: This was a retrospective study on ultrasound features, antenatal diagnosis, in‐utero intervention and long term outcome of pregnancies at risk of Haemoglobin Bart's hydrops foetalis syndrome attending prenatal diagnosis from 2000 to 2019 at Tsan Yuk Hospital in Hong Kong. Results: Among 390 foetuses from 373 at‐risk pregnancies, 122 (31%) prenatal invasive procedures were performed and 65 affected foetuses were diagnosed antenatally. For foetuses with ultrasound features of anaemia, the diagnostic yield of BHFS was 73%. Cardiomegaly carried a positive predictive value of 65.2% while its absence had the highest negative predictive value (96.0%). Three women having affected foetuses continued pregnancy and received intrauterine transfusion beginning 20 weeks of gestation. All babies were born alive and non‐hydropic. They were managed with regular transfusion and cured by haematopoietic stem cell transplantation. Conclusions: Absence of ultrasound features of anaemia had high negative predictive value for alpha thalassaemia major. Couple at risk of having affected foetus could be offered serial ultrasound surveillance. Invasive testing for pregnancies with features of foetal anaemia provided high diagnostic yield. Intrauterine transfusion corrected foetal anaemia and allowed long term transfusion free survival without significant neurological sequelae following postnatal transplant therapy. Key points: What is already known about this topic? Survival is possible for fetuses affected by Hemoglobin Bart's disease Intrauterine transfusion is available to correct fetal anaemia What this study add? Universal antenatal screening of thalassaemia should be employed in population with high prevalence Timely antenatal diagnosis provides an option for intrauterine transfusion to improve perinatal outcome and long term survival for those that choose to continue the pregnancy Transfusion should be commenced at or before 20 weeks of gestation when hemoglobin level is invariably low and can be tailored according to the trend of MCA PSV level